Leadership with care – Constructing responsibility as ‘shared caring’ in a complex public service - Hasu, Mervi; Lehtonen, Mikko (Scandinavian Journal of Public Administration, 2014)
The article investigates the pattern of influence enacted by shop-floor service workers and line managers in a public sector organisation which have been affected by New Public Management changes. Applying the concepts of care (caring) and trust, we expand the concept of the relational influence pattern originating from leadership theory. We supplement our analysis with the sensitive methodology of studying activities in shop-floor work, namely experiences of transitions on the micro-level among a group of employees, managers and clients. The results show that the caring observed in the group is shared among the individuals, it supports their collective responsibility, and exhibits trust relationships that have been created through shared experiences. Qualitative evidence illustrates that shared caring can be a pattern of relational, embodied leadership influence, directed to nurture, improve or help the situation of others in the work community. The pattern had evolved naturally through shared and expected, foreseeable experiences. We suggest the notion of leadership with care to describe this type of relational leadership influence.